Some Aspects of Evaluating Road Improvements in Congested Areas - Thomson, J. M. (Econometrica, 1970)
[All over the world economists are busy evaluating major road proposals and other transport projects. But this work is largely confined to rural areas because the methods used are inappropriate for evaluating big transport schemes in towns, where traffic congestion is a dominating consideration. This paper discusses congestion as an economic problem of demand and supply, expressed as simple functions of the cost of travel, in time and money, to the road user. Road expansion in congested cities often seems to achieve nothing but more congestion. This paper demonstrates how this arises as a process of market equilibrium, and how one can assess the benefits of the road expansion in this situation. The paper then considers how the evaluation of road schemes would be affected if direct road pricing were introduced into cities as a means of controlling congestion.]